71+10 New Science Project Junior (With Cd) : Learning Science- The Fun Way (V&S Publishers, 2016)
Science, as we all know refers to a body of knowledge itself, of the type that can be rationally explained and reliably applied. Science is a unique combination of Theory and Practice. A thorough knowledge of this subject is almost impossible without proper practical demonstrations which are also termed as Scientific Experiments or Projects. In this book, 71+10 New Science Projects (Junior), the author has taken up the simple facts and principles of Science, such as: Air Pressure, Volume and Density, Gravitational Force of the Earth, Surface Area of Solids, Fun experiments with Matchsticks, Water, Glass Bottle, Dishwashing Liquid, Oil, Candle, Balloon, etc., which are easily available for children and projected them in a simple and lucid language for the readers, particularly the school kids who can easily perform these experiments at home or school , of course with the help and guidance of their parents, elders or teachers. The book is meant for children of all age groups, particularly from 6 to 13, who can perform and experience the thrill of these fun-filled experiments as well as learn the basic principles of Science easily and quickly. Therefore, this book is a must read for all school kids, especially those from classes, five to nine to learn as well enjoy conducting all the 81 Fascinating Projects listed in the book, each explaining or proving some scientific theory or law. So go ahead children, enjoy reading, learning and experimenting!